2022
DOI: 10.3390/su141610116
|View full text |Cite
|
Sign up to set email alerts
|

Circular Economy in the Context of Food Losses and Waste

Abstract: Although consumption is one of the most important elements of any economy, including those that are developing, excessive consumerism is becoming increasingly common today, often resulting in the phenomenon of food waste. Food waste is a multi-aspect issue. It is a topical problem of varying nature and intensity, particularly for the environment, the economy, and society. In this context, efforts were made to emphasize the importance of the idea of a circular economy, due to the fact that the positive effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 82 publications
0
9
0
1
Order By: Relevance
“…The presented model and the literature expanded on in the Results section demonstrate the necessity of CE adoption in the KSA and its relevance to the country's environmental sustainability and economic development. Previous studies in this field have various aspects of the CE concept [120], including the perspectives of citizens, as revealed via surveys [121,122], and the trends and patterns of a CE in the food sector [55]. Nevertheless, the current paper is novel in that it features a KSA-specific CE model, mapping out issues in the KSA's food sector and presenting CE strategies that managers, policymakers, and even households can adopt.…”
Section: Discussionmentioning
confidence: 99%
“…The presented model and the literature expanded on in the Results section demonstrate the necessity of CE adoption in the KSA and its relevance to the country's environmental sustainability and economic development. Previous studies in this field have various aspects of the CE concept [120], including the perspectives of citizens, as revealed via surveys [121,122], and the trends and patterns of a CE in the food sector [55]. Nevertheless, the current paper is novel in that it features a KSA-specific CE model, mapping out issues in the KSA's food sector and presenting CE strategies that managers, policymakers, and even households can adopt.…”
Section: Discussionmentioning
confidence: 99%
“…This shows the empathy and sensitivity of the young generation to other people in the global dimension as well as to the dangers and problems of hunger and social inequalities regardless of their country of origin. On the other hand, another study showed that despite the fact that many consumers seem to be aware of the dilemma of excessive food discarding in their households and recognizing their active role in preventing this socio-economic problem, the food waste is still very high [66].…”
Section: Discussionmentioning
confidence: 99%
“…As shown by Table 1, although the representation of R-imperatives for CE ranges from 3 R to 10 R (Sohal and De Vass, 2022;Reike et al, 2018), the empirical literature interprets CE implementation by using the reduce, reuse and recycle concepts separately and applying them to a such specific activity. Previous literature has spent emphasis on analyzing factors affecting consumers behavior to reduce food waste (Dudziak et al, 2022;Varese et al, 2022) or recycle food by-products (Alonso-Muñoz et al, 2022;Cattaneo et al, 2019;Coderoni and Perito, 2021), also defining the Consumer Effort Index (CEI) by looking at CE categories (Paparella et al, 2023). Other studies focused on analyzing consumers' willingness to reduce the intake of…”
Section: Study Backgroundmentioning
confidence: 99%
“…, 2018), the empirical literature interprets CE implementation by using the reduce, reuse and recycle concepts separately and applying them to a such specific activity. Previous literature has spent emphasis on analyzing factors affecting consumers behavior to reduce food waste (Dudziak et al. , 2022; Varese et al.…”
Section: Study Backgroundmentioning
confidence: 99%